Clinical Manifestations and Cerebrospinal Fluid Status in Ocular Syphilis. (2nd January 2019) - Lapere, Steven; Mustak, Hamzah; Steffen, Jonel
ABSTRACT: Purpose : To review the clinical manifestations, cerebrospinal fluid findings and outcomes of patients diagnosed with ocular syphilis. Methods : Retrospective case review of all patients treated with ocular syphilis at Groote Schuur Hospital in Cape Town, South Africa between January 2008 and January 2013. Results : A total of 77 eyes of 49 patients were included. Panuveitis was the most common presenting sign (48.9%). A lumbar puncture was performed on 37 patients (75.5%) and 64.8% (24/37) of samples had positive treponemal testing (CSF-FTA) while 24.3% (9/37) had positive non-treponemal testing (CSF-VDRL). Elevated CSF lymphocyte cell count was a strong predictor of neurosyphilis (p = 0.06 for CSF-FTA positive samples and p = 0.03 for CSF-VDRL positive samples). Conclusion : The majority of patients (64.8%) who underwent lumbar puncture had cerebrospinal fluid findings suggestive of neurosyphilis. Elevated CSF lymphocyte cell count and total protein count are highly suggestive of neurosyphilis.